Faktor Produksi yang Berhubungan dengan Kontaminasi Coliform pada Jajanan Es Dawet di Kecamatan Banguntapan Bantul Yogyakarta - Ubaidillah Ubaidillah (Health Sciences and Pharmacy Journal, 2017)
Background: Drops can be contaminated by pathogenic bacteria and thus require certain standards to ensure consumer viability. Water and raw materials of ice making contaminated by pathogenic bacterial gastrointestinal pathogens are very dangerous to drink, especially water derived from wells that are less qualified microbiological quality. The purpose: of this study is to describe the conditions of making school snacks especially dawet ice and analyze the relationship of bacteriological quality factors of raw materials, personal hygiene, environmental conditions and knowledge of the production of packaging ice. Method: The method used is Cross Sectional with 30 samples, tested coliform contamination. Risk factors in this study are bacteriological quality of water, ice water, raw materials such as, dawet, coconut milk, sanitation tool / packaging, hand washing habits, knowledge, and treatment of water heating. The results were analyzed using univariate, bivariate and multivariate multiple logistic regression analysis. Results: How to wash tools / containers, knowledge of water-borne diseases and heating treatment, is a risk factor, while education level, hand washing habit, is not a risk factor. In terms of raw materials, dawet, water, ice cubes and coconut milk is a risk factor for coliform contamination, whereas guladan water and pH is not a risk factor for coliform contamination.